Evaluating the efficacy of pre-visit behavior modeling videos on pediatric patient compliance - Mahmoud Ahmed, Neveen; Alhassan, Sultan Awadh; Otayn, Waseem Ahmed; Alqahtani, Ghada Saeed; Zaydan, Afrah Moraya Al; Alhussain, Abdullah Nasser; Alghamdi, Shahad Asaad; Nogali, Nermin Ahmed; Alnimasi, Raya Mubarak; Alhejaili, Manar Abdulaziz; Almotiery, Amal Bandar (International Journal Of Community Medicine And Public Health, 2025)
Pre-visit behavior modeling videos technique is considered a promising non-pharmacological preparation for various types of medical procedures in pediatric healthcare. However, there are some significant challenges, including pediatric patient non-compliance. This challenge may result from various factors, such as pediatric anxiety, fear, or limited understanding of medical procedures. These factors lead to elevated rates of incomplete treatment, prolonged appointment durations, dependence on pharmacological intervention, and increased caregiver and parent stress, including sedation medications. Pre-visit modeling videos had emerged as a practical and child-friendly intervention, which familiarizes pediatric patients with the intended medical procedure and the healthcare environment. This article aims to critically assess the data from studies on the application of modeling videos and their compliance in pediatric patients, and it additionally aims to provide recommendations to increase this technique's compliance and care efficiency and to reduce pediatric patients’ anxiety. Furthermore, procedure completion and caregiver satisfaction will be discussed. Pre-visit modeling videos significantly increase cooperative behavior and decrease sedation use and procedure time. Additionally, age-appropriate and caregiver-engaged videos assist in decreasing anxiety. Numerous studies indicate that modeling videos were equally effective as tell-show-do and live modeling techniques; however, the modeling video method is scalable and resource-efficient. Variable intervention design, exposure timing, and outcome measurements limit generalizability despite promising findings. This review includes that pre-visit behavior modeling videos assist in pediatric behavioral management.